The morpho-climatic events in metropolitan of MDQ: a social and recurring construction - Estacio, Jairo (2013)
The presence of mud flow events, collapses and floods in the Metropolitan District of Quito (MDQ), are not explained only by events related to the physical and climatic characteristics of the MDQ as rainfall, relief and the drainage extension witch forms most of the urban consolidated zone. The anthropic activities, the usual practices of the population and the way that the local actors are managing the territory, have produced a transformation of fragile spaces through the forms of occupation and use of the land. A consequence of these recurrent processes is the increasing number of morpho-climatic events that are occurring every year in the MDQ, events that sometimes overcome the response capacities of the MDQ Municipality. In order to deal with this problem, it is necessary to improve the decisional tools and to incorporate them in the processes of territorial management. The present study presents how these tools were created in order to strengthen the decisional power at the scale of the District, considering the most relevant anthropic actions. The obtained results represent the starting point of a refinement work of these tools adapted for more precise scales and fragile spaces of the MDQ.